IMPLEMENTATION OF RELIGIOUS CHARACTER EDUCATION BASED ON PESANTREN HOUSING AT SMP NURUL MUTTAQIN PURWOREJO - Ribah, Muhammad Ato Ibnu; Aprillia, Teya; Daimah, Daimah; Wibowo, Adi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The dynamics of the development of Education in Indonesia has always been colored by various problems which until now continue to be homework together. The problem is related to the Education system, curriculum, quality of graduates, well-being and integrity of educators, infrastructure, costs, and accountability of Education institutions and managers. In addition to these problems, our education is also faced with the problem of the moral decadence of the younger generation. One of the causes of this problem is that educational institutions are still not optimal in carrying out their role. Educational institutions in Indonesia are judged to give a very large portion to the transmission of knowledge, but less or even forget the development of attitudes, values and behavior in learning. Similarly, in the evaluation process, the cognitive dimension becomes the main yardstick to determine the level of student performance. As a result, educational institutions are able to produce graduates who have extensive knowledge but care less about the social environment around them. Ironically, this educational practice also takes place in a madrasah, which is an Islamic educational institution. Madrasas should emulate the efforts made by pesantren in terms of instilling character, namely through habituation, discipline, learning process and integration in learning materials.